Considering health literacy in cardiovascular disease management: a qualitative study on healthcare professionals' and patients' perspectives - Adèle Perrin; Eléonore Damiolini; Anne-Marie Schott; Jéremy Zermati; Estelle Bravant; François Delahaye; Alexandra L. Dima; Julie Haesebaert (BMC, 2022)
Abstract Background Implementing practices adapted to patient health literacy (HL) is a promising avenue for improving their outcomes in the context of cardiovascular diseases (CVD). The health communication skills of healthcare professionals (HCPs) and the quality of information provided are essential for low-HL patients. We aimed to explore HCP knowledge about HL, patients' and HCPs' views on current practices regarding low-HL patients, and facilitators and barriers to adapting communication to patients' HL level, in order to prepare the implementation of a complex intervention dedicated to improve CVD management for low-HL patients. Methods We conducted face-to-face semi-structured interviews with HCPs practicing in cardiology units and patients hospitalized for CVD. The study design and analysis were based on the Theory of Planned Behavior for HCPs and on the framework of Health Literacy and Health Action for patients. Deductive and inductive thematic analysis were used. Barriers and facilitators were structured into an Ishikawa fishbone diagram and implementation strategies were selected to address resulting themes from the Expert Recommendations for Implementing Change (ERIC). Results Fifteen patients and 14 HCPs were interviewed. HCPs had partial knowledge of HL dimensions. Perceptions of HCPs and patients were not congruent regarding HCP-patient interactions and information provided by hospital and community HCPs. HCPs perceived they lacked validated tools and skills, and declared they adapted spontaneously their communication when interacting with low-HL patients. Patients expressed unmet needs regarding communication during hospital discharge and at return to home. Conclusion To implement HL-tailored practices in this setting, our results suggest that several implementation strategies will be valuable at individual (engaging patients and their family), interactional (educating and training of HCPs about HL), and organizational levels (creating a multidisciplinary HCP interest group dedicated to HL). Trial registration ClinicalTrials.gov, (NCT number) NCT03949309, May 10, 2019.